INSTITUTION MODEL ON MANAGEMENT OF REGIONAL WASTE PROCESSING SITE - Samsuri; Maulana, Lucky Hikmat; Warizal (International Journal of Psychosocial Rehabilitation, 2020)
The main problem of waste management in urban areas is the limited land available for the location of the Final Waste Processing Site (TPAS). To overcome this problem, the city government cooperated with the district government in handling the final processing of waste together (TPAS Regional) with TPAS locations in the district area. This condition occurs in the cities of Yogyakarta and Denpasar, which have collaborated in the management of Regional TPAS with surrounding districts. Yogyakarta City Government cooperates with Sleman Regency and Bantul Regency, known as TPAM Regional Kartamantul. While the Denpasar City Government collaborated with Bandung Regency, Gianyar Regency, and Tabanan Regency, known as TPAS Regional Sarbagita. In the implementation of the Regional TPAS, it is less effective due to among others: institutional structures that are too large, lack of coordination between institutions, overlapping of leading tasks, and institutional functions between districts if problems occur. This study aims to choose the right institutional model for regional TPAS management so that it can develop and be independent. This research uses exploratory methods and discussed using SWOT analysis. The SWOT analysis results show that the Regional Technical Implementation Unit (UPTD) of Province is superior to the District UPTD. The existence of UPTD institutions under the Provincial Government as the manager of the Regional TPAS facilitates supervision and control in the field. Districts/cities involved in cooperation can send waste to the TPAS location, with only a tipping fee charged according to the volume of waste sent. Whereas the transportation of debris from the waste source to the TPAS location remains the responsibility of each district/city. This research conducted in two areas, TPAM Regional Kartamantul and TPAS Regional Sarbagita. The most appropriate institution to manage Regional TPAS to be able to develop and be independent is the Provincial UPTD by applying the Financial Management Pattern of the Regional Public Service Board (PPK-BLUD).